Neoliberal Discourse on the Webpages of English-Medium Vocational Education Schools and Coding Bootcamps in Sweden - Metreveli, Anna (Critical Education, 2025)
Vocational education and training (VET) programs in Sweden blend classroom instruction and internships, while coding bootcamps offer accelerated adult education in computer science. These institutions increasingly teach in English, mirroring the shift towards English-medium Instruction (EMI) in higher education. Consequently, most EMI scholarship is focused on higher education. This paper investigates how ten Swedish EMI schools are discursively constructed on their webpages, employing reflective thematic analysis to uncover three primary themes: the schools’ affinity with success, the uniqueness of their students, and the schools’ teaching methods. The analysis reveals the schools’ strong affinities with the neoliberal language and ideology, suggesting an alignment with the discourse of academic capitalism in higher and vocational EMI contexts. This paper discusses the similarities and differences in the dominance of neoliberal language and ideology in both educational settings, highlighting broader implications for critical education.